The Role of Solid Amendments in Promoting the Accelerated Anaerobic Bioremediation of Groundwater Containing High Concentrations of cis- 1,2-Dichloroethene - FREIM, JOHN; BICKMORE, CLINT; VARNELL, RICHARD; FOGEL, SAM; A. NEWMAN, WILLIAN (Águas Subterrâneas, 2013)
In-situ anaerobic bioremediation is an elegant method for decontaminating groundwater containing halogenated hydrocarbons and other toxic contaminants. Successful bioremediation is predicated on establishing and maintaining groundwater that is deoxygenated, electrochemically reducing and pH neutral. Solid remediation amendments, including zero valent metals and carbonate buffers, provide an opportunity to establish and maintain the fertile environment that supports effective anaerobic bioremediation. Zero valent metals are strong reductants that can rapidly render the affected groundwater deoxygenated and electrochemically reducing. Similarly, calcium carbonate is a slow-acting base that has long-term buffering capabilities to help maintain pH neutral conditions. This approach was successfully employed at a large industrial facility in the Southwestern U.S. where prior remediation efforts had resulted in a slowly degrading cis-1,2-dichloroethene plume with concentrations as high as 250 mg/L. This remediation program involved adding sub-micrometer zero valent metal, calcium carbonate and emulsified vegetable oil (EVO) to 60 injection wells within a 120 meters long by 30 meters wide treatment area. The product’s small particle size allowed for a uniform distribution of the solid remediation amendments within the treatment area at injection pressures ranging from 200-600 kPa. Shortly after applying the remediation amendments, an acid-resistant microbial consortium containing dehalococcoides etheneogenes was added to 15 of the injection wells. Within seven months of product application, c-1,2-DCE concentrations had decreased by over 99% in the most contaminated monitoring well with a similar response in down gradient monitoring wells. Vinyl chloride concentrations peaked about six months after product application and have since degraded mostly to ethene, indicating that a biotic pathway was the primary degradation mechanism.